Clinical and radiographic outcomes of total hip replacement with poly(2-methacryloyloxyethyl phosphorylcholine)-grafted highly cross-linked polyethylene liners: Three-year results of a prospective consecutive series. Issue 2 (March 2015) - Takatori, Yoshio; Moro, Toru; Ishihara, Kazuhiko; Kamogawa, Morihide; Oda, Hiromi; Umeyama, Takashige; Kim, Yoon Taek; Ito, Hideya; Kyomoto, Masayuki; Tanaka, Takeyuki; Kawaguchi, Hiroshi; Tanaka, Sakae
Abstract Objectives. This study aimed to evaluate the clinical safety and wear-resistance of the novel highly cross-linked polyethylene (HXLPE) acetabular liner with surface grafting of poly(2-methacryloyloxyethyl phosphorylcholine) (PMPC) at 3 years after total hip replacement (THR). Methods. Eighty consecutive patients underwent cementless THR using a 26-mm diameter cobalt–chromium–molybdenum alloy femoral head and a PMPC-grafted HXLPE liner for the bearing couplings. We evaluated the clinical and radiographic outcomes of 76 patients at 3 years after the index surgery. Results. The clinical results at 3 years were equivalent to a Harris hip score of 95.6 points. No adverse events were associated with the implanted PMPC-grafted HXLPE liner, and no periprosthetic osteolysis was detected. The mean femoral head penetration rate was 0.002 mm/year, representing marked reduction compared with other HXLPE liners. Conclusions. A PMPC-grafted HXLPE liner is a safe option in THR and probably reduces the generation of wear particles.